Global Analysis of microRNA-like RNAs Reveals Differential Regulation of Pathogenicity and Development in Fusarium oxysporum HS2 Causing Apple Replant Disease - Ruxin Zhao; Xiangmin Suo; Xianglong Meng; Yanan Wang; Pengbo Dai; Tongle Hu; Keqiang Cao; Shutong Wang; Bo Li (Journal of Fungi)
This study investigated the expression profiles of microRNA-like RNAs (milRNAs) in Fusarium oxysporum HS2 (FoHS2), a key pathogen causing Apple replant disease (ARD), across spore to mycelium formation stages. Using small RNA sequencing (sRNA-seq) and bioinformatics, we identified and analyzed milRNAs, revealing their targeting of 2364 mRNAs involved in 20 functional categories, including metabolic and cellular processes, based on gene ontology (GO) analysis. An analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that these mRNAs are related to carbohydrate and amino acid metabolism pathways. Notably, the highest number of differentially or specifically expressed milRNAs (DEmilRNAs/SEmilRNAs) was found during the spore stage, with FoHS2-milR19 targeting genes encoding histone acetyltransferases, methyltransferases, and cell wall-degrading enzymes (CWDEs), which are crucial for growth, development, and pathogenicity. We validated the reliability of our sRNA-seq data and the expression of target genes using stem-loop RT-PCR and qRT-PCR. Our results highlight the stage-specific expression of milRNAs in FoHS2, particularly in the spore stage, suggesting a key role in regulating host life activities and providing a theoretical basis for developing RNA-based pesticides to control ARD.